Low-VOC (volatile organic compound) epoxy resin coating based on nano modification technology and preparation method thereof

By introducing nanomaterials into epoxy resin coatings to form a three-dimensional network structure, the problems of high VOC emissions, performance limitations and poor construction performance of traditional coatings are solved, and the high performance and versatility of low VOC epoxy resin coatings are achieved, satisfying the needs of high VOC Environmental protection and performance requirements of modern industry.

CN119161785AInactive Publication Date: 2024-12-20HUBEI BOYI WEIYE SITE DESIGN ENG CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411413478.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional solvent-based epoxy resin coatings have problems such as high VOC emissions, limited performance, poor construction performance and single functionality, which are difficult to meet the needs of modern industry for environmentally friendly, high-performance and multifunctional coatings.

Method used

Using low VOC epoxy resin coating based on nanomodification technology, a three-dimensional network structure is formed by adding nanomaterials such as nanotitanium dioxide, antibacterial microspheres, magnetic materials, graphene nanosheets, thermal fillers, etc., and combining low VOC diluents and additives. , improve the hardness, wear resistance, thermal conductivity and construction performance of the paint.

Benefits of technology

It significantly reduces the harmful gas emissions of the paint during construction and curing, improves the hardness, wear resistance, corrosion resistance and thermal conductivity of the paint, enhances the overall performance of the paint, and meets the needs of environmental protection, efficiency and multifunction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161785A_ABST
    Figure CN119161785A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of low-VOC epoxy resin, in particular to a low-VOC epoxy resin coating based on a nano modification technology and a preparation method of the low-VOC epoxy resin coating, solves the defects in the prior art, and comprises the following components: 50-60 parts of an epoxy resin base material, 2-5 parts of nano titanium dioxide, 1-3 parts of antibacterial microspheres, 0.5-2 parts of a nanoscale magnetic material and 1-3 parts of graphene nanosheets. According to the low-VOC epoxy resin coating and the preparation method thereof, the low-VOC epoxy resin coating which is low in VOC emission and excellent in antibacterial property and heat-conducting property is prepared through careful proportioning and a nano modification technology, and the requirements of the market for environment-friendly and high-performance coatings are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of low-VOC epoxy resins, and in particular to a low-VOC epoxy resin coating based on nano-modification technology and a preparation method thereof. Background Art

[0002] With the increasing global environmental awareness and the continuous improvement of coating performance requirements, traditional solvent-based epoxy resin coatings are gradually unable to meet the requirements of modern industrial production and environmental regulations due to their high volatile organic compound (VOC) emissions and potential harm to the environment. Therefore, the development of low-VOC, high-performance epoxy resin coatings has become a research hotspot in the current coating field. Nano-modification technology, as an emerging material modification method, can significantly improve the various properties of epoxy resin coatings by introducing nanoparticles into epoxy resin coatings, while reducing VOC emissions, providing new ideas for the development of environmentally friendly high-performance coatings.

[0003] Deficiencies in the prior art:

[0004] 1. High VOC emissions: Traditional solvent-based epoxy resin coatings produce a large amount of volatile organic compounds (VOCs) during production and use, which not only harms human health, but also pollutes the natural environment and is not in line with the development trend of green environmental protection.

[0005] 2. Performance limitations: In certain special environments, such as high temperature and high humidity, the weather resistance and mechanical properties of traditional epoxy resin coatings are difficult to meet the needs of long-term use.

[0006] 3. Poor construction performance: Some solvent-based epoxy resin coatings have problems such as poor leveling and slow drying during the construction process, which affects the construction efficiency and coating quality.

[0007] 4. Single functionality: Traditional epoxy resin coatings have relatively single functions and cannot meet the needs of modern industry for multifunctional coatings.

[0008] Therefore, we proposed a low-VOC epoxy resin coating based on nano-modification technology and a preparation method thereof to solve the above problems. Summary of the invention

[0009] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a low-VOC epoxy resin coating based on nano-modification technology and a preparation method thereof.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] The low-VOC epoxy resin coating based on nano-modification technology includes the following components in parts by weight: 50-60 parts of epoxy resin base material, 2-5 parts of nano-titanium dioxide, 1-3 parts of antibacterial microspheres, 0.5-2 parts of nano-magnetic materials, 1-3 parts of graphene nanosheets, 2-5 parts of nano-thermal conductive fillers, 10-20 parts of low-VOC diluent, 0.5-1.5 parts of leveling agent, 1-2 parts of anti-aging agent, and 0.5-1.5 parts of thickener.

[0012] As the preferred technical solution:

[0013] The low-VOC epoxy resin coating based on nano-modification technology as described above includes the following components in parts by weight: 55 parts of epoxy resin base material, 3 parts of nano-titanium dioxide, 2 parts of antibacterial microspheres, 1 part of nano-magnetic material, 2 parts of graphene nanosheets, 3 parts of nano-thermal conductive fillers, 15 parts of low-VOC diluent, 1 part of leveling agent, 1.5 parts of anti-aging agent, and 1 part of thickener.

[0014] As described above, the low-VOC epoxy resin coating based on nano-modification technology, the epoxy resin base material is one of bisphenol A epoxy resin and aliphatic epoxy resin, the nano titanium dioxide is one of rutile nano titanium dioxide and anatase nano titanium dioxide, the antibacterial microspheres are one of silver ion-containing microspheres and copper ion-containing microspheres, the nano-scale magnetic material is one of ferroferric oxide and hematite, the graphene nanosheets are one of single-layer graphene nanosheets and multi-layer graphene nanosheets, the nano-scale thermal conductive filler is one of boron nitride and aluminum oxide, the low-VOC diluent is one of an aqueous diluent and a low-toxic organic solvent, the leveling agent is one of an organosilicon leveling agent and a fluorocarbon leveling agent, the anti-aging agent is one of a hindered amine light stabilizer and an ultraviolet absorber, and the thickener is one of an inorganic thickener and an organic thickener.

[0015] As described above, the low VOC epoxy resin coating based on nano-modification technology has an epoxy value of 0.48 to 0.52 eq / 100 g, a particle size of nano-titanium dioxide of 15 to 50 nm, a particle size of antibacterial microspheres of 200 to 300 nm, a particle size of nano-magnetic material of 40 to 60 nm, and a specific surface area of ​​graphene nanosheets of 500 to 3000 m 2 / g, the particle size of the nano-scale thermal conductive filler is 10-500nm, the VOC content of the low VOC diluent is 10-50g / L, the molecular weight of the leveling agent is 1000-3000, and the pH value of the thickener is 7-9.

[0016] In the low-VOC epoxy resin coating based on nano-modification technology as described above, the surface of the nano-magnetic material is coated with a layer of organic matter, so that its surface can be closely combined with the epoxy resin base material, and the nano-magnetic material forms a primary pre-network structure in the coating. Under the action of the magnetic field, the nano-magnetic material is oriented, and functional groups are introduced on the surface of the graphene nanosheets, which are combined with the epoxy resin base material through hydrogen bonding to form a secondary pre-network structure in the coating, which is interspersed with the epoxy resin molecular chain to form a three-dimensional network structure, wherein the three-dimensional network structure density of the final coating is set to ρ final ,but:

[0017]

[0018] Among them, m solid is the total mass of solid components in the coating, v paint is the total volume of the coating, m coating-effective is the mass of the coating layer that effectively contributes to the network structure, m nano-total is the total mass of the nanomagnetic material and its coating, m graphene is the mass of graphene nanosheets, N bonds is the total number of chemical bonds formed in the coating, V paint-effective is the volume of coating that effectively contributes to the network structure;

[0019] The second aspect of the present invention provides a method for preparing a low VOC epoxy resin coating based on nano-modification technology, comprising the following steps:

[0020] S1: Select epoxy resin base material, place it in a vacuum drying oven, set the vacuum degree and temperature, and remove the moisture and residual solvent in the base material;

[0021] S2: Then, respectively, nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets, and nano-thermal conductive fillers are added to a container containing a low-VOC diluent, and an ultrasonic disperser is started;

[0022] S3: First add the pre-treated epoxy resin base material into the stirring container, then add the leveling agent pre-dissolved in the low VOC diluent, increase the stirring speed while adding, and keep stirring for a while;

[0023] S4: Add the dispersed solution one by one in order and speed under continuous stirring, and keep stirring for a while after each addition;

[0024] S5: Add thickener during stirring and observe the change in coating viscosity while adding;

[0025] S6: Add the anti-aging agent during the stirring process and keep stirring for a while to ensure that the anti-aging agent is evenly dispersed in the coating;

[0026] S7: Gradually add low-VOC diluent during stirring, and observe the change in coating viscosity while adding;

[0027] S8: The mixed paint is filtered through a filter, and the filtered paint is left to stand for a period of time to allow bubbles to rise and disappear.

[0028] As the preferred technical solution:

[0029] As described above, the low-VOC epoxy resin coating based on nano-modification technology and the preparation method thereof, in said S2, nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets and nano-scale thermal conductive fillers are then added to a container containing a low-VOC diluent, and the ultrasonic disperser is started, the ultrasonic frequency is set to 20-40kHz, the power is set to 50-200W, and the dispersion time is set to 0.5-1 hour.

[0030] As described above, the low-VOC epoxy resin coating based on nano-modification technology and the preparation method thereof, in said S3, the pretreated epoxy resin base material is first added to the stirring container, and then the leveling agent pre-dissolved in the low-VOC diluent is added, the initial stirring speed is set to 500-1000 rpm, gradually increased to 1500-3000 rpm, and the stirring time is maintained for 15-30 minutes.

[0031] As described above, the low-VOC epoxy resin coating based on nano-modification technology and the preparation method thereof, the epoxy resin base material has an n+1-level branching structure, the surface of the nano-titanium dioxide is treated with a silane coupling agent, one end of the silane coupling agent reacts with the hydroxyl group on the surface of the nano-titanium dioxide to form a chemical bond, and the other end reacts with the functional group in the epoxy resin base material, interweaving together to form a three-dimensional network structure.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adopts low-VOC diluent, which reduces the emission of harmful gases during the construction and curing process of the coating, is environmentally friendly, helps to improve indoor air quality, and protects human health. By adding high-performance nanomaterials such as nano titanium dioxide and graphene nanosheets, the hardness and wear resistance of the coating are improved, and the service life of the coating is extended. With the help of nano-modification technology, the coating is improved in terms of hardness, wear resistance, corrosion resistance, etc. The addition of nano-scale thermal conductive fillers improves the thermal conductivity of the coating, which helps to transfer and dissipate heat faster.

[0033] Nano-titanium dioxide and graphene nanosheets not only improve the hardness and wear resistance of the coating, but also enhance the corrosion resistance of the coating. This synergistic effect allows the coating to maintain its integrity and stability for a longer time when it is subjected to external impact and chemical erosion.

[0034] The present invention improves the overall performance of the coating by reinforcing the nano materials and synergizing the nano materials with the base material and the additives. The coating has certain advantages in environmental protection, high efficiency and multi-function. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a line graph of thermal performance data of the embodiments and comparative examples of the present invention;

[0036] Figure 2 It is a line graph of viscosity data of the embodiments and comparative examples of the present invention;

[0037] Figure 3 It is a bar chart of impact resistance data of the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by ordinary technicians in the field to which the invention belongs. When there is a conflict, the definitions in this specification shall prevail. "When mass, concentration, temperature, time, or other values ​​or parameters are expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36 , 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, and all decimal values ​​between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction. "

[0039] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0040] The low-VOC epoxy resin coating based on nano-modification technology includes the following components in parts by weight: 50-60 parts of epoxy resin base material, 2-5 parts of nano-titanium dioxide, 1-3 parts of antibacterial microspheres, 0.5-2 parts of nano-magnetic materials, 1-3 parts of graphene nanosheets, 2-5 parts of nano-thermal conductive fillers, 10-20 parts of low-VOC diluent, 0.5-1.5 parts of leveling agent, 1-2 parts of anti-aging agent, and 0.5-1.5 parts of thickener.

[0041] Among them, the epoxy resin base material is one of bisphenol A epoxy resin and aliphatic epoxy resin, the nano titanium dioxide is one of rutile nano titanium dioxide and anatase nano titanium dioxide, the antibacterial microspheres are one of silver ion-containing microspheres and copper ion-containing microspheres, the nano-scale magnetic material is one of ferroferric oxide and hematite, the graphene nanosheets are one of single-layer graphene nanosheets and multi-layer graphene nanosheets, the nano-scale thermal conductive filler is one of boron nitride and aluminum oxide, the low-VOC diluent is one of an aqueous diluent and a low-toxic organic solvent, the leveling agent is one of an organosilicon leveling agent and a fluorocarbon leveling agent, the anti-aging agent is one of a hindered amine light stabilizer and an ultraviolet absorber, and the thickener is one of an inorganic thickener and an organic thickener.

[0042] The epoxy value of the epoxy resin base material is 0.48 to 0.52 eq / 100 g, the particle size of nano titanium dioxide is 15 to 50 nm, the particle size of the antibacterial microsphere is 200 to 300 nm, the particle size of the nano-magnetic material is 40 to 60 nm, and the specific surface area of ​​the graphene nanosheet is 500 to 3000 m 2 / g, the particle size of the nano-scale thermal conductive filler is 10-500nm, the VOC content of the low VOC diluent is 10-50g / L, the molecular weight of the leveling agent is 1000-3000, and the pH value of the thickener is 7-9.

[0043] The surface of the nanomagnetic material is coated with a layer of organic matter, so that its surface can be closely combined with the epoxy resin base material. The nano-magnetic material forms a primary pre-network structure in the coating. Under the action of the magnetic field, the nano-magnetic material is oriented, and functional groups are introduced on the surface of the graphene nanosheets. It combines with the epoxy resin base material through hydrogen bonding to form a secondary pre-network structure in the coating, which is interlaced with the epoxy resin molecular chain to form a three-dimensional network structure. The density of the three-dimensional network structure of the final coating is set to ρ final ,but:

[0044]

[0045] Among them, m solid is the total mass of solid components in the coating, v paint is the total volume of the coating, m coating-effectiveis the mass of the coating layer that effectively contributes to the network structure, m nano-total is the total mass of the nanoscale magnetic material and its coating, m graphene is the mass of graphene nanosheets, N bonds is the total number of chemical bonds formed in the coating, V paint-effective is the volume of coating that effectively contributes to the network structure;

[0046] The surface of the nanomagnetic material is coated with a layer of organic material (silane coupling agent). The purpose of this coating layer is to make the surface energy of the nanomagnetic material closely bonded with the epoxy resin base material, thereby enhancing the overall performance of the material. The nanoscale magnetic material forms a pre-network structure in the coating. This shows that the nanomagnetic material is not randomly distributed in the coating, but arranged in an orderly manner. This arrangement helps to enhance the structural strength of the coating. Under the action of the magnetic field, the nanomagnetic material will be arranged in a directional manner, further enhancing the orderliness and stability of the pre-network structure. Functional groups (hydroxyl groups) are introduced into the surface of the graphene nanosheets. The functional groups can bind to the epoxy resin base material through hydrogen bonding, thereby enhancing the interaction between the graphene nanosheets and the epoxy resin. After the graphene nanosheets are combined with the epoxy resin base material, a secondary pre-network structure is formed in the coating. This structure is interspersed with the primary pre-network structure, and together they constitute the basic network framework of the coating.

[0047] Finally, the nanomagnetic materials and graphene nanosheets interweave with the epoxy resin molecular chains to form a complex three-dimensional network structure, which gives the coating excellent mechanical properties, thermal stability and chemical stability.

[0048] The epoxy resin-based coating of the present invention, wherein the total volume v paint For 100 ml.

[0049] Total mass of solid components in the coating m solid The weight of the composite is 50 grams, which includes nano-scale magnetic materials, graphene nanosheets, their coating layers and solid components in an epoxy resin base.

[0050] The total mass of the nanomagnetic material and its coating layer m nano-total The weight of the nanomagnetic material is 10 grams, of which the weight of the nanomagnetic material itself is 8 grams and the weight of the coating layer is 2 grams.

[0051] The mass of graphene nanosheet m graphene is 5 grams.

[0052] The effective contribution of the coating mass to the network structure is m coating-effective It is 1.5 grams (not all coating layers here effectively contribute to the network structure).

[0053] The total number of chemical bonds formed in the coating N bondsIt is 5×1022.

[0054] The volume of coating that effectively contributes to the network structure V paint-effective The coating has 90 ml of water (there will be some voids or parts that do not participate in the formation of the network structure).

[0055] The final ρ final The value is 12.3, which is a high density, indicating that the network structure in the coating is relatively tight, and the chemical bonds and intermolecular interactions are strong. This means that the coating has good mechanical properties, such as hardness, wear resistance and scratch resistance.

[0056] Embodiment 1

[0057] The low-VOC epoxy resin coating based on nano-modification technology includes the following components in parts by weight: 50 parts of epoxy resin base material, 2 parts of nano-titanium dioxide, 1 part of antibacterial microspheres, 0.5 parts of nano-magnetic materials, 1 part of graphene nanosheets, 2 parts of nano-thermal conductive fillers, 10 parts of low-VOC diluents, 0.5 parts of leveling agents, 1 part of anti-aging agents, and 0.5 parts of thickeners.

[0058] The epoxy resin base material is bisphenol A epoxy resin (Shandong Deyuan Epoxy Technology Co., Ltd.), the nano titanium dioxide is rutile nano titanium dioxide (Shijiazhuang Jinghuang Technology Co., Ltd.), the antibacterial microspheres are silver ion-containing microspheres (Zibo Bona Technology Development Co., Ltd.), the nano-scale magnetic material is ferrosoferric oxide (Zhejiang Zhitianawei New Materials Co., Ltd.), the graphene nanosheets are single-layer graphene nanosheets (Shanghai Liantian Materials Technology Co., Ltd.), the nano-scale thermal conductive filler is boron nitride (Jiangsu Tianxing New Materials Co., Ltd.), the low VOC diluent is an aqueous diluent, the leveling agent is an organosilicon leveling agent, the anti-aging agent is a hindered amine light stabilizer (Guangzhou Zhenwei Chemical Technology Co., Ltd.), and the thickener is an inorganic thickener (Shijiazhuang Changtai Zinc Industry Co., Ltd.).

[0059] The low VOC epoxy resin coating based on nano-modification technology and the preparation method thereof proposed by the present invention include the following steps:

[0060] S1: Select epoxy resin base material, place it in a vacuum drying oven, set the vacuum degree to 0.05MPa, set the temperature to 80℃, and keep the drying time for 4 hours to ensure that the moisture and residual solvent in the base material are effectively removed;

[0061] S2: Then, nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets and nano-thermal conductive fillers are added to the container containing low-VOC diluent, and the ultrasonic disperser is started, and the ultrasonic frequency is set to 20 kHz, the power is set to 50 W, and the dispersion time is set to 0.5 hours;

[0062] S3: First add the pretreated epoxy resin base material into the stirring container, and then add the leveling agent pre-dissolved in the low VOC diluent. The initial stirring speed is set to 500 rpm, and gradually increased to 1500 rpm, and the stirring time is maintained for 15 minutes;

[0063] S4: Under continuous stirring, first add the nano-scale thermal conductive filler, then add nano-titanium dioxide, graphene nanosheets, antibacterial microspheres and nano-scale magnetic materials in sequence, and keep stirring for 5 minutes after each addition;

[0064] S5: Add thickener during the stirring process and observe the change in the viscosity of the coating while adding. The viscosity of the coating should gradually increase;

[0065] S6: Add the anti-aging agent during the stirring process, and set the stirring time to 10 minutes to ensure that the anti-aging agent is evenly dispersed in the coating;

[0066] S7: Gradually add low-VOC diluent during stirring, and observe the change in the viscosity of the paint while adding. The viscosity of the paint should gradually decrease;

[0067] S8: The mixed paint is filtered through a filter, and the filtered paint is left to stand for 0.5 hours to allow bubbles to rise and disappear naturally.

[0068] Embodiment 2

[0069] The low-VOC epoxy resin coating based on nano-modification technology includes the following components in parts by weight: 60 parts of epoxy resin base material, 5 parts of nano-titanium dioxide, 3 parts of antibacterial microspheres, 2 parts of nano-magnetic materials, 3 parts of graphene nanosheets, 5 parts of nano-thermal conductive fillers, 20 parts of low-VOC diluent, 1.5 parts of leveling agent, 2 parts of anti-aging agent, and 1.5 parts of thickener.

[0070] The epoxy resin base material is aliphatic epoxy resin (Shenzhen Jiadida Chemical Co., Ltd.), the nano titanium dioxide is anatase nano titanium dioxide (Shanghai Titan Technology Co., Ltd.), the antibacterial microspheres are copper ion-containing microspheres (Zibo Bona Technology Development Co., Ltd.), the nano-scale magnetic material is hematite (Beijing Dekedao Gold Technology Co., Ltd.), the graphene nanosheets are multilayer graphene nanosheets (Ningbo Moxi Technology Co., Ltd.), the nano-scale thermal conductive filler is alumina (Ningbo Moxi Technology Co., Ltd.), the low VOC diluent is a low-toxic organic solvent, the leveling agent is a fluorocarbon leveling agent, the anti-aging agent is a UV absorber, and the thickener is an organic thickener.

[0071] The low VOC epoxy resin coating based on nano-modification technology and the preparation method thereof proposed by the present invention include the following steps:

[0072] S1: Select epoxy resin base material, place it in a vacuum drying oven, set the vacuum degree to 0.1MPa, set the temperature to 120℃, and keep the drying time for 8 hours to ensure that the moisture and residual solvent in the base material are effectively removed;

[0073] S2: Then, nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets and nano-thermal conductive fillers are added to the container containing low-VOC diluent, and the ultrasonic disperser is started, and the ultrasonic frequency is set to 40 kHz, the power is set to 200 W, and the dispersion time is set to 1 hour;

[0074] S3: First add the pretreated epoxy resin base material into the stirring container, and then add the leveling agent pre-dissolved in the low VOC diluent. The initial stirring speed is set to 1000 rpm, and gradually increased to 3000 rpm, and the stirring time is maintained for 30 minutes;

[0075] S4: Under continuous stirring, first add the nano-scale thermal conductive filler, then add nano-titanium dioxide, graphene nanosheets, antibacterial microspheres and nano-scale magnetic materials in sequence, and keep stirring for 10 minutes after each addition;

[0076] S5: Add thickener during the stirring process and observe the change in the viscosity of the coating while adding. The viscosity of the coating should gradually increase;

[0077] S6: Add the anti-aging agent during the stirring process, and set the stirring time to 20 minutes to ensure that the anti-aging agent is evenly dispersed in the coating;

[0078] S7: Gradually add low-VOC diluent during stirring, and observe the change in the viscosity of the paint while adding. The viscosity of the paint should gradually decrease;

[0079] S8: The mixed paint is filtered through a filter, and the filtered paint is left to stand for 1 hour to allow bubbles to rise and disappear naturally.

[0080] Embodiment 3

[0081] The low-VOC epoxy resin coating based on nano-modification technology includes the following components in parts by weight: 52 parts of epoxy resin base material, 3 parts of nano-titanium dioxide, 1.5 parts of antibacterial microspheres, 1 part of nano-magnetic material, 1.5 parts of graphene nanosheets, 3 parts of nano-thermal conductive fillers, 13 parts of low-VOC diluent, 0.8 parts of leveling agent, 1.2 parts of anti-aging agent, and 0.8 parts of thickener.

[0082] The epoxy resin base material is bisphenol A epoxy resin, the nano titanium dioxide is rutile nano titanium dioxide, the antibacterial microspheres are silver ion-containing microspheres, the nano-scale magnetic material is ferrosoferric oxide, the graphene nanosheets are single-layer graphene nanosheets, the nano-scale thermal conductive filler is boron nitride, the low-VOC diluent is an aqueous diluent, the leveling agent is an organic silicon leveling agent, the anti-aging agent is a hindered amine light stabilizer, and the thickener is an inorganic thickener.

[0083] The low VOC epoxy resin coating based on nano-modification technology and the preparation method thereof proposed by the present invention include the following steps:

[0084] S1: Select epoxy resin base material, place it in a vacuum drying oven, set the vacuum degree to 0.06MPa, set the temperature to 90°C, and keep the drying time for 5 hours to ensure that the moisture and residual solvent in the base material are effectively removed;

[0085] S2: Then, nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets and nano-thermal conductive fillers are added to the container containing low-VOC diluent, and the ultrasonic disperser is started, and the ultrasonic frequency is set to 25 kHz, the power is set to 80 W, and the dispersion time is set to 0.6 hours;

[0086] S3: First add the pretreated epoxy resin base material into the stirring container, and then add the leveling agent pre-dissolved in the low VOC diluent. The initial stirring speed is set to 600 rpm, and gradually increased to 2000 rpm, and the stirring time is maintained for 20 minutes;

[0087] S4: Under continuous stirring, first add the nano-scale thermal conductive filler, then add nano-titanium dioxide, graphene nanosheets, antibacterial microspheres and nano-scale magnetic materials in sequence, and keep stirring for 6 minutes after each addition;

[0088] S5: Add thickener during the stirring process and observe the change in the viscosity of the coating while adding. The viscosity of the coating should gradually increase;

[0089] S6: Add the anti-aging agent during the stirring process, and set the stirring time to 12 minutes to ensure that the anti-aging agent is evenly dispersed in the coating;

[0090] S7: Gradually add low-VOC diluent during stirring, and observe the change in the viscosity of the paint while adding. The viscosity of the paint should gradually decrease;

[0091] S8: The mixed paint is filtered through a filter, and the filtered paint is left to stand for 0.6 hours to allow bubbles to rise and disappear naturally.

[0092] Embodiment 4

[0093] The low-VOC epoxy resin coating based on nano-modification technology includes the following components in parts by weight: 58 parts of epoxy resin base material, 4 parts of nano-titanium dioxide, 2.5 parts of antibacterial microspheres, 1.8 parts of nano-magnetic materials, 2.5 parts of graphene nanosheets, 4 parts of nano-thermal conductive fillers, 18 parts of low-VOC diluent, 1.3 parts of leveling agent, 1.8 parts of anti-aging agent, and 1.3 parts of thickener.

[0094] The epoxy resin base material is aliphatic epoxy resin, the nano titanium dioxide is anatase nano titanium dioxide, the antibacterial microspheres are copper ion-containing microspheres, the nano-scale magnetic material is hematite, the graphene nanosheets are multilayer graphene nanosheets, the nano-scale thermal conductive filler is aluminum oxide, the low VOC diluent is a low-toxic organic solvent, the leveling agent is a fluorocarbon leveling agent, the anti-aging agent is an ultraviolet absorber, and the thickener is an organic thickener.

[0095] The low VOC epoxy resin coating based on nano-modification technology and the preparation method thereof proposed by the present invention include the following steps:

[0096] S1: Select epoxy resin base material, place it in a vacuum drying oven, set the vacuum degree to 0.08MPa, set the temperature to 110℃, and keep the drying time for 7 hours to ensure that the moisture and residual solvent in the base material are effectively removed;

[0097] S2: Then, nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets and nano-thermal conductive fillers are added to the container containing low-VOC diluent, and the ultrasonic disperser is started, and the ultrasonic frequency is set to 35 kHz, the power is set to 150 W, and the dispersion time is set to 0.8 hours;

[0098] S3: First add the pretreated epoxy resin base material into the stirring container, then add the leveling agent pre-dissolved in the low VOC diluent, set the initial stirring speed to 800 rpm, gradually increase to 2800 rpm, and keep stirring for 25 minutes;

[0099] S4: Under continuous stirring, first add the nano-scale thermal conductive filler, then add nano-titanium dioxide, graphene nanosheets, antibacterial microspheres and nano-scale magnetic materials in sequence, and keep stirring for 9 minutes after each addition;

[0100] S5: Add thickener during the stirring process and observe the change in the viscosity of the coating while adding. The viscosity of the coating should gradually increase;

[0101] S6: Add the anti-aging agent during the stirring process, and set the stirring time to 18 minutes to ensure that the anti-aging agent is evenly dispersed in the coating;

[0102] S7: Gradually add low-VOC diluent during stirring, and observe the change in the viscosity of the paint while adding. The viscosity of the paint should gradually decrease;

[0103] S8: The mixed paint is filtered through a filter, and the filtered paint is left to stand for 0.9 hours to allow bubbles to rise and disappear naturally.

[0104] Embodiment 5

[0105] On the basis of Example 4, the epoxy resin base material has an n+1 level branching structure, and the surface of the nano-titanium dioxide is treated with a silane coupling agent. One end of the silane coupling agent reacts with the hydroxyl group on the surface of the nano-titanium dioxide to form a chemical bond, and the other end reacts with the functional group in the epoxy resin base material, interweaving together to form a three-dimensional network structure.

[0106] S1: First, an epoxy resin base material with an n+1-level branching structure is selected. Then, the selected epoxy resin base material is placed in a vacuum drying oven, the vacuum degree is set to 0.08 MPa, the temperature is set to 110°C, and the drying time is maintained for 7 hours to ensure that the moisture and residual solvent in the base material are effectively removed.

[0107] S2: In terms of processing nanomaterials, first use a silane coupling agent to treat the surface of nano titanium dioxide. Add nano titanium dioxide powder to a flask containing anhydrous ethanol, disperse it evenly through ultrasonic dispersion, add a certain amount of silane coupling agent to the nano titanium dioxide dispersion, and control the amount of silane coupling agent to 10% of the mass of nano titanium dioxide. Place the dispersion on a magnetic stirrer and stir at 80°C for 1 hour. During the reaction, one end of the silane coupling agent reacts with the hydroxyl group on the surface of nano titanium dioxide to form a chemical bond, and the other end can react with the epoxy functional group in the epoxy resin base. In this way, when nano titanium dioxide is added to epoxy resin, the two can be intertwined to form a three-dimensional network structure, thereby enhancing the performance of the coating.

[0108] Next, the treated nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets and nano-thermal conductive fillers were added to a container containing a low-VOC diluent. The ultrasonic disperser was then started, with the ultrasonic frequency set to 35kHz, the power set to 150W and the dispersion time set to 0.8 hours to ensure that the nanomaterials were evenly dispersed in the diluent.

[0109] S3: Add the pre-treated epoxy resin base material into the stirring container, and then add the leveling agent pre-dissolved in the low VOC diluent. The initial stirring speed is set to 800 rpm, and gradually increased to 2800 rpm, and the stirring time is maintained for 25 minutes to ensure that the leveling agent and the epoxy resin base material are fully mixed.

[0110] S4-S8: The steps are the same as those in Example 4.

[0111] Example 5 Through the treatment of silane coupling agent, nano titanium dioxide and epoxy resin base material are interwoven to form a three-dimensional network structure. This structure enhances the hardness and wear resistance of the coating, and also helps to improve the impact resistance, scratch resistance and aging resistance of the coating. The nanomaterials in the three-dimensional network structure can effectively transmit and disperse stress, preventing the coating from cracking or falling off when subjected to external forces.

[0112] Comparative Example 1

[0113] The low VOC epoxy resin coating based on nano-modification technology and the preparation method thereof are basically the same as those in Example 4, except that the application of nano-titanium dioxide in the low VOC epoxy resin coating is removed.

[0114] Comparative Example 2

[0115] The low VOC epoxy resin coating and preparation method thereof based on nano-modification technology are basically the same as those in Example 4, except that the application of antibacterial microspheres and nano-magnetic materials in the low VOC epoxy resin coating is removed.

[0116] Comparative Example 3

[0117] The low-VOC epoxy resin coating and preparation method thereof based on nano-modification technology are basically the same as those in Example 4, except that the application of nano-scale thermal conductive fillers in the low-VOC epoxy resin coating is removed.

[0118] Comparative Example 4

[0119] The low VOC epoxy resin coating based on nano-modification technology and the preparation method thereof are basically the same as those in Example 4, except that the application of nano-titanium dioxide and graphene nanosheets in the low VOC epoxy resin coating is removed.

[0120] The low VOC epoxy resin coatings based on nano-modification technology prepared in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 4 were tested, and the test standards are as follows;

[0121] GB / T 9286-1998: Adhesion test. This standard stipulates that a blade is used to draw square cross grids at a certain interval and at equal distances on the coating film. The coating adhesion level is evaluated by comparing the coating peeling in the grid area.

[0122] GB / T 1730-2007: Thermal performance testing specifies the evaluation of thermal stability and crack resistance of coatings by simulating extreme temperature changes.

[0123] GB / T 1723-1993: Viscosity test. Viscosity test is one of the important indicators for evaluating the fluidity of epoxy resin coatings. Instruments such as rotational viscometer and falling ball viscometer can be used to measure the viscosity value of the coating and determine whether it is qualified based on specific application requirements.

[0124] GB / T 1732-1993: Impact resistance test, which evaluates the ability of the cured coating to resist external impact. The drop hammer impact test is used to simulate the impact force that the coating may be subjected to in actual use, and observe whether the coating has cracking, peeling, etc.

[0125] The low VOC epoxy resin coatings based on nano-modification technology of the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 4 were tested, and the results are shown in Table 1:

[0126] Table 1

[0127]

[0128] Through the above Table 1, it can be determined directly that in Examples 1 to 4, the thermal properties of Examples 1 to 4 are all around 210°C, showing high thermal stability, and the viscosity values ​​of Examples 1 to 4 are 518mPa·s to 520mPa·s, indicating that the coating has moderate viscosity, and the impact resistance of Examples 1 to 4 is 48kg·cm to 50kg·cm, indicating strong impact resistance, indicating that the coating can maintain its integrity when subjected to external force impact and is not prone to cracking, and the adhesion of Examples 1 to 4 is all level 1, indicating that the coating is firmly bonded to the substrate, ensuring that the coating is not easy to fall off during use. Examples 1 to 4 are excellent in thermal performance, viscosity, impact resistance and adhesion, and improve the comprehensive performance of the coating.

[0129] Reference Figure 1-3 , the thermal performance of Example 5 is 215°C, which is improved compared to Example 4. It shows that Example 5 has better stability in high temperature environment. In terms of viscosity, the viscosity of Example 5 is 525mPa·s, which is higher than 518mPa·s of Example 4. The increase in viscosity improves the uniformity and appearance quality of the coating. The impact resistance of Example 5 is 52kg·cm, which is higher than that of Example 4, indicating that the coating of Example 5 can maintain better integrity when subjected to external force impact. Finally, in terms of adhesion, both Example 5 and Example 4 are Level 1, indicating that the bonding between the coating and the substrate is very strong. Ensure that the coating is not easy to fall off or peel off during use.

[0130] In summary, compared with Example 4, Example 5 has improvements in thermal performance, viscosity and impact resistance, while maintaining excellent adhesion, making the overall performance more outstanding.

[0131] In Example 4 and Comparative Example 1, where other conditions are the same, Comparative Example 1 removes the application of nano titanium dioxide in low VOC epoxy resin coatings. The thermal performance of Comparative Example 1 is 195°C, which is lower than 210°C of Example 4, indicating that the coating of Comparative Example 1 is more likely to deteriorate under higher temperature conditions, thereby shortening the service life of the coating. The viscosity of Comparative Example 1 is 480mPa·s, which is lower than 518mPa·s of Example 4. The low viscosity causes the coating to be too fluid during construction and difficult to control. The impact resistance of Comparative Example 1 is 45kg·cm, which is lower than 48kg·cm of Example 4. It shows that the coating of Comparative Example 1 is more likely to crack, peel off, etc. when impacted by external forces. The adhesion of Comparative Example 1 is level 2, which is inferior to level 1 of Example 4. The reduction in adhesion indicates that the bonding between the coating and the substrate is not strong enough, causing the coating to fall off or peel off easily. The adhesion decreases because nano-titanium dioxide helps to strengthen the bonding between the coating and the substrate; the viscosity decreases because the reduction of nanoparticles reduces the cohesion of the coating; and the impact resistance decreases because the reinforcing effect of nano-titanium dioxide is weakened.

[0132] Comparative Example 2 removes the application of antibacterial microspheres and nano-magnetic materials in low-VOC epoxy resin coatings. The thermal performance of Comparative Example 2 is 190°C, which is lower than 210°C of Example 4, indicating that the coating of Comparative Example 2 is more likely to deteriorate or fail. The viscosity of Comparative Example 2 is 490mPa·s, which is lower than 518mPa·s of Example 4. The construction performance and thickness uniformity of the coating of Comparative Example 2 deteriorate. The impact resistance of Comparative Example 2 is 42kg·cm, which is lower than 48kg·cm of Example 4. It shows that the coating of Comparative Example 2 is more likely to crack, peel off, etc. when impacted by external forces, and its mechanical strength and durability are poor. The adhesion of Comparative Example 2 is level 3, which is lower than level 1 of Example 4, indicating that the bonding between the coating of Comparative Example 2 and the substrate is not strong enough. It shows that the adhesion, thermal performance, viscosity and impact resistance have all decreased after the antibacterial microspheres and nano-magnetic materials have been removed.

[0133] Comparative Example 3 removes the application of nano-scale thermal conductive fillers in low VOC epoxy resin coatings. The thermal performance of Comparative Example 3 is 185°C, which is lower than 210°C of Example 4, indicating that under higher temperature conditions, the coating of Comparative Example 3 is more prone to deterioration or failure than Example 4, and its thermal stability is poor. The viscosity of Comparative Example 3 is 480mPa·s, which is lower than 518mPa·s of Example 4. The low viscosity of Comparative Example 3 leads to excessive fluidity of the coating, which increases the difficulty of construction. The impact resistance of Comparative Example 3 is 45kg·cm, which is slightly lower than 48kg·cm of Example 4, indicating that the coating of Comparative Example 3 is weakened in its ability to resist cracking and peeling when subjected to external force impact. The adhesion of Comparative Example 3 is level 2, while the adhesion of Example 4 is level 1. It shows that the bonding between its coating and the substrate is not as strong as that of Example 4. After removing the nano-scale thermal conductive fillers, the thermal performance is significantly reduced, and the adhesion, viscosity and impact resistance are all reduced.

[0134] Comparative Example 4 removes the application of nano titanium dioxide and graphene nanosheets in low VOC epoxy resin coatings. The thermal performance of Comparative Example 4 is 175°C, which is lower than 210°C of Example 4, indicating that under higher temperature environments, the coating of Comparative Example 4 is more likely to deteriorate or fail than Example 4. The viscosity of Comparative Example 4 is 470mPa·s, which is lower than 518mPa·s of Example 4. The lower viscosity of Comparative Example 4 will cause the fluidity of the coating to be too strong, increasing the difficulty of construction. The impact resistance of Comparative Example 4 is 40kg·cm, which is lower than 48kg·cm of Example 4. It shows that the coating of Comparative Example 4 is weaker than Example 4 in resisting cracking and peeling when subjected to external force impact. The adhesion of Comparative Example 4 is level 3, while the adhesion of Example 4 is level 1. The adhesion of Comparative Example 4 is poor, indicating that the bonding between its coating and the substrate is not as strong as that of Example 4. It shows that nano titanium dioxide and graphene nanosheets play a synergistic role in the coating, so their removal leads to a significant decrease in the performance of the coating.

[0135] In summary, Example 4 has improvements in thermal performance, viscosity, impact resistance, adhesion, etc. compared with Comparative Examples 1 to 4. In practical applications, the requirements of high-performance coatings can be met.

[0136] The present invention uses nano titanium dioxide, which has extremely small particle size and high specific surface area, to effectively fill the tiny pores and defects in the epoxy resin coating to form a more compact and uniform coating structure. The small size effect of the nanoparticles enables it to better penetrate into the tiny depressions and cracks on the metal surface, forming stronger physical bonding and chemical bonding, thereby significantly improving the adhesion between the coating and the substrate. This strong adhesion can ensure that the coating is not easy to fall off or peel off during long-term use. Environmentally friendly materials such as low-VOC diluents are used in the preparation process to reduce the emission of volatile organic compounds (VOC). This not only helps to reduce the harm to the environment and human health, but also meets the requirements of current environmental protection laws and regulations.

[0137] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Low VOC epoxy resin coating based on nano-modification technology, characterized in that: The invention comprises the following components in parts by weight: 50-60 parts of epoxy resin base material, 2-5 parts of nano titanium dioxide, 1-3 parts of antibacterial microspheres, 0.5-2 parts of nano magnetic material, 1-3 parts of graphene nano sheets, 2-5 parts of nano thermal conductive fillers, 10-20 parts of low VOC diluent, 0.5-1.5 parts of leveling agent, 1-2 parts of anti-aging agent and 0.5-1.5 parts of thickener.

2. The low VOC epoxy resin coating based on nano-modification technology according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 55 parts of epoxy resin base material, 3 parts of nano titanium dioxide, 2 parts of antibacterial microspheres, 1 part of nano magnetic material, 2 parts of graphene nano sheets, 3 parts of nano thermal conductive fillers, 15 parts of low VOC diluent, 1 part of leveling agent, 1.5 parts of anti-aging agent and 1 part of thickener.

3. The low VOC epoxy resin coating based on nano-modification technology according to claim 1, characterized in that: The epoxy resin base material is one of bisphenol A epoxy resin and aliphatic epoxy resin, the nano titanium dioxide is one of rutile nano titanium dioxide and anatase nano titanium dioxide, the antibacterial microspheres are one of silver ion-containing microspheres and copper ion-containing microspheres, the nano-scale magnetic material is one of ferroferric oxide and hematite, the graphene nanosheets are one of single-layer graphene nanosheets and multi-layer graphene nanosheets, the nano-scale thermal conductive filler is one of boron nitride and aluminum oxide, the low-VOC diluent is one of an aqueous diluent and a low-toxic organic solvent, the leveling agent is one of an organosilicon leveling agent and a fluorocarbon leveling agent, the anti-aging agent is one of a hindered amine light stabilizer and an ultraviolet absorber, and the thickener is one of an inorganic thickener and an organic thickener.

4. The low VOC epoxy resin coating based on nano-modification technology according to claim 1, characterized in that: The epoxy value of the epoxy resin base material is 0.48-0.52 eq / 100 g, the particle size of the nano titanium dioxide is 15-50 nm, the particle size of the antibacterial microsphere is 200-300 nm, the particle size of the nano-magnetic material is 40-60 nm, and the specific surface area of ​​the graphene nanosheet is 500-3000 m 2 / g, the particle size of the nano-scale thermal conductive filler is 10-500nm, the VOC content of the low VOC diluent is 10-50g / L, the molecular weight of the leveling agent is 1000-3000, and the pH value of the thickener is 7-9.

5. The low VOC epoxy resin coating based on nano-modification technology according to claim 1, characterized in that: The surface of the nanomagnetic material is coated with a layer of organic matter, so that its surface can be closely combined with the epoxy resin base material, and the nano-magnetic material forms a primary pre-network structure in the coating. Under the action of the magnetic field, the nano-magnetic material is oriented, and functional groups are introduced on the surface of the graphene nanosheets, which are combined with the epoxy resin base material through hydrogen bonding to form a secondary pre-network structure in the coating, which is interlaced with the epoxy resin molecular chain to form a three-dimensional network structure. The density of the three-dimensional network structure of the final coating is set to ρ final ,but: Among them, m solid is the total mass of solid components in the coating, v paint is the total volume of the coating, m coating-effective is the mass of the coating layer that effectively contributes to the network structure, m nano-total is the total mass of the nanomagnetic material and its coating, m graphene is the mass of graphene nanosheets, N bonds is the total number of chemical bonds formed in the coating, V paint-effective It is the volume of coating that effectively contributes to the network structure.

6. A method for preparing a low-VOC epoxy resin coating based on nano-modification technology according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Select epoxy resin base material, place it in a vacuum drying oven, set the vacuum degree and temperature, and remove the moisture and residual solvent in the base material; S2: Then, respectively, nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets, and nano-thermal conductive fillers are added to a container containing a low-VOC diluent, and an ultrasonic disperser is started; S3: First add the pre-treated epoxy resin base material into the stirring container, then add the leveling agent pre-dissolved in the low VOC diluent, increase the stirring speed while adding, and keep stirring for a while; S4: Add the dispersed solution one by one in order and speed under continuous stirring, and keep stirring for a while after each addition; S5: Add thickener during stirring and observe the change in coating viscosity while adding; S6: Add the anti-aging agent during the stirring process and keep stirring for a while to ensure that the anti-aging agent is evenly dispersed in the coating; S7: Gradually add low-VOC diluent during stirring, and observe the change in coating viscosity while adding; S8: The mixed paint is filtered through a filter, and the filtered paint is left to stand for a period of time to allow bubbles to rise and disappear.

7. The method for preparing a low VOC epoxy resin coating based on nano-modification technology according to claim 6, characterized in that: In S2, nano-titanium dioxide, antibacterial microspheres, nano-magnetic materials, graphene nanosheets and nano-thermal conductive fillers are respectively added to a container containing a low-VOC diluent, an ultrasonic disperser is started, the ultrasonic frequency is set to 20-40 kHz, the power is set to 50-200 W, and the dispersion time is set to 0.5-1 hour.

8. The method for preparing a low VOC epoxy resin coating based on nano-modification technology according to claim 6, characterized in that: In S3, the pretreated epoxy resin base is first added to the stirring container, and then the leveling agent pre-dissolved in the low VOC diluent is added, the initial stirring speed is set to 500-1000 rpm, and gradually increased to 1500-3000 rpm, and the stirring time is maintained for 15-30 minutes.

9. The method for preparing a low VOC epoxy resin coating based on nano-modification technology according to claim 6, characterized in that: The epoxy resin base material has an n+1-level branching structure. The surface of the nano-titanium dioxide is treated with a silane coupling agent. One end of the silane coupling agent reacts with the hydroxyl group on the surface of the nano-titanium dioxide to form a chemical bond, and the other end reacts with the functional group in the epoxy resin base material to form a three-dimensional network structure.

Citation Information

Patent Citations

  • Conductive anticorrosive paint for power grounding grid and preparation method thereof

    CN105907243A

  • Preparation method of magnetic coating

    CN108531082A

  • Nano modified epoxy resin floor coating and preparation method thereof

    CN109486345A

  • Graphene and nanometer titanium dioxide composite coating material, preparation method and applications thereof

    CN110872457A

  • Packaging structure and packaging method thereof, and display device

    CN113130810A